Efficacy of High-Dose Vitamin C Infusion on Outcomes in Sepsis Requiring Mechanical Ventilation: A Double-Blind Randomized Controlled Trial - Wessam A. El Driny; Ibrahim M. Esmat; Sara M. Shaheen; Nagwa A. Sabri (Anesthesiology Research and Practice)
Background. Critically ill patients have an increased requirement for vitamin C in sepsis and these patients have low levels of vitamin C. The researchers validated the efficacy of high-dose vitamin C intravenous infusion (IVI) in patients with sepsis requiring mechanical ventilation. Methods. Forty patients were randomly assigned to 2 groups (20 each) in a 1 : 1 ratio in accordance with the vitamin C treatment regimen: Group I (GI): patients received 1.5 g/6 h vitamin C in 50 ml of dextrose 5% in water (D5W) IVI over 30 minutes for 4 consecutive days; Group II (GII): patients received 100 mg vitamin C/day as a first single dose in 50 ml of D5W IVI over 30 minutes and the other three subsequent doses were 50 ml of plain D5W IVI over 30 minutes for 4 consecutive days. Primary outcomes were the change in sequential organ failure assessment (SOFA) score at day 7, the incidence of ventilator-associated pneumonia (VAP), and the plasma vitamin C level. The glutathione peroxidase (GPX) activity, C-reactive protein (CRP) level, duration of vasopressor therapy, and 28-day mortality were secondary outcomes. Results. The change in SOFA score at day 7 showed a significant difference between GI and GII (p<0.001). The incidence of early VAP was significantly lower in GI (p=0.044). Vitamin C levels showed a significant rise in GI at day 1 and day 4 (p<0.001 and p<0.001, respectively). GPX activity of day 4 and day 7 was significantly higher in GI (p=0.005 and p=0.014, respectively). CRP levels of day 4 and day 7 were significantly higher in GII (p<0.001 and p<0.001, respectively). There was a significant difference in 28-day mortality (p=0.038) and duration of vasopressor therapy (p=0.033) in GI compared to GII. Conclusion. The early use of high-dose vitamin C intravenous infusion in patients with sepsis requiring mechanical ventilation in combination with the standard treatment for sepsis lowered the incidence of VAP, increased the antioxidant status, and improved the illness severity. Trial Registration. This trial is registered with ClinicalTrials.gov Identifier (NCT04029675).